Bubble momentum plume as a possible mechanism for an early breakdown of the seasonal stratification in the northern North Sea. (December 2015) - Nauw, Janine; Linke, Peter; Leifer, I.
Abstract: The presence of a seasonal thermocline likely plays a key role in restraining methane released from a seabed source in the deeper water column, thereby inhibiting exchange to the atmosphere. The bubble plume itself, however, generates an upward motion of fluid, e.g. upwelling and may thereby be partially responsible for an early breakdown of the seasonal thermocline. Measurements at site 22/4b, located at (57°55′N, 1°38′E) in the UK Central North Sea, 200 km east of the Scottish mainland, where gas is still being released since a blow out in 1990, have been used to identify the generation of the seasonal thermocline, and thus, the depth of the upper mixed layer and its breakdown in autumn. Data derived from two landers, containing an Acoustic Doppler Current Profiler and a Conductivity Temperature Depth recorder, were used to determine the mixed layer depth and the breakdown of the thermocline. Mixing of upper layer fluid into the lower layer has been inferred from large amplitude variations in the near-bottom temperature. The ADCPs estimate velocity profiles in four beam directions using Doppler shifted frequency from acoustic pings sent out and received by four different transducers in a specific configuration. Besides that, the intensity of the backscattered sound per transducer is also recorded. Bubbles from the nearby plume contaminate the signal during part of the tidal cycle, but in bubble free periods, the mixed layer depth can be estimated using the acoustic backscatter signal as local maxima. Results show that the thermocline broke down between mid-October and early November, several weeks earlier than the breakdown of the thermocline in nearby/comparable areas, likely caused by bubble-induced downwelling at the site. The early breakdown of the thermocline was accompanied by multiple occurrence of a strong jet-like structure, associated with the seasonal tidal mixing front. Highlights: Bubble-plume induced early breakdown of the thermocline in the northern North Sea. Thermocline detection algorithm using acoustic backscatter of an ADCP. Strong jet-like structures related to passage of the tidal mixing front. Large upward bubble-momentum plume velocities of 33 cm/s.